Tinjauan Yuridis terhadap Illegal Fishing Menggunakan Bahan Peledak di Kabupaten Indramayu Berdasarkan Undang-Undang Nomor 45 Tahun 2009 tentang Perikanan - Rhifa Hasna Nisrina; Mahmud, Ade (Bandung Conference Series: Law Studies, 2024)
Abstract. Indonesia is an archipelagic country with a total of 17,480 islands in its jurisdiction, consisting of both large and small islands. Therefore, the sea plays a crucial role in the unity and cohesion of Indonesia. In addition, the vastness of Indonesia's sea waters makes it abundant in wealth and various natural resources contained therein. The wealth of Indonesia's seas often attracts the attention of individuals to enjoy it illegally. Therefore, Indonesia is often faced with violations of the law that occur in its maritime waters. One of the maritime law violations that often occur is illegal fishing, including the use of environmentally damaging equipment, including the use of explosives. In West Java Province alone, precisely in the Indramayu Regency area, based on Handling data from the North Marine and Fisheries Resources Supervision and Handling Agency (PSDKPWU) from 2021 to 2023, there were 34 cases of fish capture using prohibited equipment, including explosives, which resulted in almost all coral reefs and other marine habitats being damaged. The comprehensive Law No. 45 of 2009 on Fisheries regulates the management and supervision of fisheries, including fisheries management areas, fisheries management activities, fisheries research and development, fisheries counseling, fisheries courts, investigation, prosecution, and fisheries inspection, as well as special criminal provisions within the scope of fisheries. However, the implementation of these legal regulations is often not followed by some individuals who engage in illegal fishing. Therefore, this paper will discuss the legal enforcement against perpetrators of illegal fishing using explosives in Indramayu Regency based on Law No. 45 of 2009 on Fisheries and efforts to overcome illegal fishing using explosives in Indramayu Regency. The purpose is to understand the implementation of the law based on Law No. 45 of 2009 on Fisheries and its efforts in handling perpetrators of illegal fishing using explosives in Indramayu Regency. The research method used is a normative juridical approach, with a descriptive analytical research specification, data collection through literature research, and analysis method using qualitative descriptive analysis. Abstrak. Indonesia is an archipelagic country with a total of 17,480 islands in its jurisdiction, consisting of both large and small islands. Therefore, the sea plays a crucial role in the unity and cohesion of Indonesia. Di samping itu, ukuran perairan laut Indonesia menyebabkan banyaknya kekayaan laut dan berbagai sumber daya alam yang ada di dalamnya. Kekayaan laut Indonesia sering kali menarik perhatian individu untuk dapat menikmatinya secara melanggar hukum atau tidak sah. Oleh karena itu, Indonesia sering menghadapi pelanggaran hukum yang terjadi di perairan lautnya. Salah satu pelanggaran hukum di laut yang sering terjadi adalah penangkapan ikan secara tidak sah atau juga dikenal sebagai penangkapan ikan ilegal. Bahkan banyak orang yang melakukan tindakan itu menggunakan alat yang berdampak negatif pada lingkungan, termasuk penggunaan bahan peledak. Di Provinsi Jawa Barat, khususnya di Kabupaten Indramayu, berdasarkan data Penanganan dari Pengawasan Sumber Daya Kelautan dan Perikanan Wilayah Utara (PSDKPWU) dari Tahun 2021 hingga Tahun 2023 tercatat 34 kasus penangkapan ikan menggunakan alat yang dilarang, termasuk bahan peledak yang menyebabkan kerusakan pada terumbu karang dan habitat laut lainnya. Undang-Undang Nomor 45 Tahun 2009 tentang Perikanan secara menyeluruh mengatur tentang pengelolaan dan pengawasan di bidang perikanan, termasuk wilayah pengelolaan perikanan, kegiatan pengelolaan perikanan, penelitian dan pengembangan perikanan, penyuluhan perikanan, pengadilan perikanan, penyidikan, penuntutan, dan pemeriksaan perikanan, serta ketentuan pidana khusus dalam lingkup perikanan. Namun, penerapan peraturan hukum tersebut seringkali tidak diikuti oleh beberapa orang yang melakukan illegal fishing. Sehubungan dengan hal tersebut, Penulis akan membahas mengenai penindakan hukum terhadap pelaku penangkapan ikan ilegal dengan menggunakan bahan peledak di Kabupaten Indramayu berdasarkan Undang-Undang Nomor 45 Tahun 2009 tentang Perikanan dan upaya untuk mengatasi penangkapan ikan ilegal dengan menggunakan bahan peledak di Kabupaten Indramayu. Dengan maksud untuk mengetahui dan memahami pelaksanaan hukumnya berdasarkan Undang-Undang Nomor 45 Tahun 2009 tentang dan usahanya dalam menangani pelaku illegal fishing using bahan peledak di Kabupaten Indramayu. Dengan menggunakan metode pendekatan berupa pendekatan yuridis normatif, spesifikasi penelitian yang diterapkan bersifat deskriptif analitis, pengumpulan data melalui penelitian kepustakaan, dan metode analisis dengan cara analisis deskriptif kualitatif.